Evaluating the Current Evidence for the Efficacy of Cannabis in Symptom Management of Endometriosis-Associated Pain - Savannah Calleson Cummings; Nicole Ennis; Katie Kloss; Robyn Rosasco (Integrative Medicine Reports)
Introduction: Endometriosis is a chronic condition that affects millions of women in the United States. Chronic pain can be debilitating and complex to manage. Despite common approaches like hormonal treatments and surgery, many women continue to endure pain. Managing the chronic and multifaceted nature of endometriotic pain necessitates a comprehensive strategy. Methods: This study explores the potential of cannabis in alleviating endometriosis-related pain through an extensive literature search. Cohort studies, case-control studies, cross-sectional surveys, and systematic reviews from January 1996 to August 2022 were eligible for inclusion. Articles were then assessed and included for further analysis if they met the following criteria: (1) Population was women with endometriosis; (2) Discussed the therapeutic use of medical cannabis for endometriosis-related pain. Results: The literature search revealed 522 articles, with eight articles meeting criteria for analysis: four cross-sectional surveys, two systematic reviews, one retrospective cohort study, and one literature review. Cannabis consumption for symptom relief was common among women with endometriosis, and some even reported that the use of cannabis reduced their use of analgesics. Discussion: The use of cannabis for endometriosis-related pain holds significant promise for addressing the often-debilitating comfort experienced by those with this condition. By interacting with the endocannabinoid system, cannabis may provide relief by modulating pain perception, reducing inflammation, relaxing muscles, and alleviating neuropathic discomfort.